PENSION PAYMENT SYSTEM IN URBAN POVERTY REDUCTION PROJECT USING VISUAL BASIC 6.0 PROGRAMMING LANGUAGES - Susilowati Susilowati; Susi Wagiyati, SKom Susi Wagiyati, SKom (Jurnal Sistem Informasi, 2001)
Based on research from the running system, causing adverse effects or problems thatcan hamper KSM data processing, so it needs to implement a system that is proposedto solve the problem. Information about KSM issued become more effective andefficient and accurate data can be guaranteed. Speed the process of making reports,the ease of doing the changes to the files of SHGs, so that the utilization of hardwareand software limitations and ensure computer security device that is used for dataprocessing in the future and can support the decision-making.